Influence of ethnic traditional cultures on genetic diversity of rice landraces under on-farm conservation in southwest China. Issue 1 (December 2016) - Wang, Yanjie; Wang, Yanli; Sun, Xiaodong; Caiji, Zhuoma; Yang, Jingbiao; Cui, Di; Cao, Guilan; Ma, Xiaoding; Han, Bing; Xue, Dayuan; Han, Longzhi
Abstract Background Crop genetic resources are important components of biodiversity. However, with the large-scale promotion of mono-cropping, genetic diversity has largely been lost.Ex-situ conservation approaches were widely used to protect traditional crop varieties worldwide. However, this method fails to maintain the dynamic evolutionary processes of crop genetic resources in their original habitats, leading to genetic diversity reduction and even loss of the capacity of resistance to new diseases and pests. Therefore, on-farm conservation has been considered a crucial complement toex-situ conservation. This study aimed at clarifying the genetic diversity differences betweenex-situ conservation and on-farm conservation and to exploring the influence of traditional cultures on genetic diversity of rice landraces under on-farm conservation. Methods The conservation status of rice landrace varieties, includingIndica andJaponica, non-glutinous rice (Oryza sativa ) and glutinous rice (Oryza sativa var. glutinosa Matsum), was obtained through ethno-biology investigation method in 12 villages of ethnic groups from Guizhou, Yunnan and Guangxi provinces of China. The genetic diversity between 24 pairs of the same rice landraces from different times were compared using simple sequence repeat (SSR) molecular markers technology. The landrace paris studied were collected in 1980 and maintainedex-situ, while 2014 samples were collected on-farm in southwest of China. Results The results showed that many varieties of rice landraces have been preserved on-farm by local farmers for hundreds or thousands of years. The number of alleles (Na), effective number of alleles (Ne), Nei genetic diversity index (He) and Shannon information index (I) of rice landraces were significantly higher by 12.3–30.4 % under on-farm conservation than underex-situ conservation. Compared with theex-situ conservation approach, rice landraces under on-farm conservation programs had more alleles and higher genetic diversity. In every site we investigated, ethnic traditional cultures play a positive influence on rice landrace variety diversity and genetic diversity. Conclusion Most China's rice landraces were conserved in the ethnic areas of southwest China. On-farm conservation can effectively promote the allelic variation and increase the genetic diversity of rice landraces over the past 35 years. Moreover, ethnic traditional culture practices are a crucial foundation to increase genetic diversity of rice landraces and implement on-farm conservation.